REAKSI PASAR SAHAM DI INDONESIA SAAT DAN SETELAH PERISTIWA TARIFF WAR AMERIKA SERIKAT DAN CHINA - Andriani, Sri (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
The uncertainty surrounding tariff policies imposed by US President Donald Trump has prompted other countries, such as China, to retaliate by raising tariffs on US goods. Investors, particularly those in the capital market, have responded, as they seek to secure their funds. This study aims to determine the stock market reaction to companies included in the LQ45 index. The event study method used analyzes the stock market reaction during and after the tariff war between the US and China. Data analysis techniques used the independent sample t-test and the Wilcoxon signed-rank test. The study found that abnormal returns on stocks included in the LQ45 index responded to the policies implemented by both countries. This event prompted investors to react negatively without waiting for new policy changes between the two countries. Meanwhile, trading volume activity showed no difference in response during and after the tariff war. Investors tended to wait and see how significant the impact might be after the event.